Urban Theme Embodiment in the Novels of Charles Dickens - Osmukhina, Olga Yurievna; Tanaseichuk, Andrey Borisovich; Sharonova, Elena Aleksandrovna; Kazeeva, Elena Aleksandrovna (Journal of History Culture and Art Research, 2020)
The article analyzes the features of London image and the representation of urban theme in Charles Dickens’ novels “The Adventures of Oliver Twist”, “Dombey and Son”, “Bleak House”. As anthropomorphic characters of novels, the city acts as a full-fledged artistic image. It is established that London is a center of plot nodes contraction and appears to be versatile and multifaceted. On the one hand, it is a city in which all provincial residents rush. They dream of finding themselves here and occupying a worthy position in life. On the other hand, the writer portrays London as the personification of cold, deceitful relationships, alienation of people in high society. It combines contrasting pictures of luxury and poverty, grandeur and squalor; it lives by a separate independent life and affects the feelings and actions of heroes. The article notes that London is always accompanied by landscape sketches in Dickens’ novels. Most often, these are stable and multifunctional images of fog and cold. In the novel “The Adventures of Oliver Twist,” fog and cold become symbols of the concealment of the dirty deeds of the cruel and criminal world of London, in which the protagonist is originally immersed. In the novel “Bleak House”, they are the personification of the Supreme Court, and in “Dombey and Son”, the descriptions of cold, foggy, and gray London represent the cold of human relations that reigns in the family of financial magnate Mr. Dombey.